Effect of fast neutron irradiation on tensile properties of AISI 304 stainless steel and alloy Ti-6Al-4V - Singh B.K.; Singh V. (My University, 2025)
Effect of fast neutron irradiation at low fluence level of ∼1018ncm-2, on tensile properties of AISI 304 stainless steel and titanium alloy Ti-6Al-4V, was studied at ambient temperature. Flat tensile specimens, subjected to fast neutron irradiation to three different fluences of 0.6×1018, 1.2×1018 and 4.8×1018ncm-2, in a reactor, were tested at ambient temperature. It was observed that yield strength and tensile strength of the AISI 304 stainless steel increased marginally, upto the fluence level of 1.2×1018ncm-2, but significantly at the highest fluence of 4.8×1018ncm-2. However there was only nominal decrease in ductility due to neutron irradiation. On the other hand, in the alloy Ti-6Al-4V there was fall both in strength as well as ductility with increase in neutron fluence. Ductility was found to decrease upto the fluence of 1.2×1018ncm-2 and remained constant at higher fluences. Phase instability was revealed by X-ray diffraction in both the neutron irradiated materials. © 2011 Elsevier B.V.